Monitoring the Climate Change Impacts of Urban Agriculture in Rosario, Argentina - Piacentini, Ruben Dario Narciso (2014)
As the world population in cities has surpassed that of rural areas, urban and periurban agricul-ture (UPA) can become an important strategy, not only to feed the people, but also to mitigate climate change. In the city of Rosario, Argentina, with the support of the RUAF Foundation and the Climate and Development Knowledge Network (CDKN), a detailed study is being conducted to monitor the urban heat island, reduction in the use of food transportation and preservation and in the impact of flooding by green infrastructure